2019
DOI: 10.1017/s000711451900134x
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides in goats’ milk-based infant formula and their prebiotic and anti-infection properties

Abstract: Human milk contains an abundant supply and diverse array of oligosaccharides that are known to impart significant health benefits to the nursing infant including establishment and maintenance of a healthy gut microflora, immune development and protection against gastrointestinal infections. When breastfeeding is not possible or insufficient, infant formulas are commonly used as an alternative. However, limited information is available about the presence of naturally occurring oligosaccharides in these infant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 63 publications
(67 reference statements)
1
37
0
7
Order By: Relevance
“…The previous studies regarding the antimicrobial activity of free MOs have been mainly focused on the antiadhesive property (Coppa et al., 2006; Jantscher‐Krenn et al., 2012; Leong et al., 2019; Martin‐Sosa et al., 2002; Ryan et al., 2018). No bactericidal/bacteriostatic activity of milk free oligosaccharide against S. aureus has yet been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies regarding the antimicrobial activity of free MOs have been mainly focused on the antiadhesive property (Coppa et al., 2006; Jantscher‐Krenn et al., 2012; Leong et al., 2019; Martin‐Sosa et al., 2002; Ryan et al., 2018). No bactericidal/bacteriostatic activity of milk free oligosaccharide against S. aureus has yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the structures are different between species, especially in the levels of fucosylation and sialylation moieties (Dong, Zhou, & Mechref, 2016; Tao, DePeters, German, Grimm, & Lebrilla, 2009; Totten et al., 2012; Wu, Tao, German, Grimm, & Lebrilla, 2010). MOs have been reported to maintain the balance of intestinal microorganisms by resisting the invasion of pathogenic microorganisms and reducing the adhesion of host cells against pathogens, and therefore, decreasing incidences of neonatal diarrhea, meningitis, and other diseases (Coppa et al., 2006; Hakkarainen et al., 2005; Jantscher‐Krenn et al., 2012; Kulinich & Liu, 2016; Leong et al., 2019; Ryan, Slattery, Hickey, & Marotta, 2018). The special biological functions of MOs have been associated with their structural specificity, namely of fucosylation and sialylation (Cervantes, Newburg, & Ruiz‐Palacios, 1996; Martin‐Sosa, Martin, & Hueso, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharide-enriched fractions prepared from both stage one and stage two goats milk-based infant formula were also recently shown to significantly enhance the growth of bifidobacteria in vitro and reduce the adhesion of E. coli NCTC 10418 and Salmonella enterica subsp. enterica serovar Typhimurium to Caco-2 cells [13], possibly by acting as analogues of epithelial receptors on the gut cells [14]. In vivo studies have also indicated that ingestion of GMO by mice during gestation and lactation increased the relative abundance of bifidobacteria in the colon of their pups at weaning [15].…”
mentioning
confidence: 99%
“…Due to the advanced technologies adopted for sugar analysis such as mass spectra, a huge number of structures have been identified and characterized. Moreover, significant differences in chemical structure of free milk oligosaccharides between species, both qualitative and quantitative, were described in detail [153,[172][173][174][175]. Such extraordinary diversity is suggested to have a direct impact on eliciting a wide range of biological functions.…”
Section: Non-human Fucosylated Milk Oligosaccharidesmentioning
confidence: 99%
“…<1% [153] ok. 20% [176] 0.89-8.95% [174,178] Concentration of 2 -FL 2.7 (1.88-4.9) g/L [3] Absent [179] or present in low amounts [180] 1.12 mg/L [175] present [173] Free oligosaccharides present in domestic mammals' milk are different from the human milk oligosaccharide profile, and their concentrations are approximately 10-100 times lower than in human milk [15][16][17]174,[176][177][178] regardless of the lactation stage. In addition to the total concentration of oligosaccharides, the most spectacular differences relate to the presence of fucosylated structures, characteristic for human milk ( Table 2).…”
Section: -50% [3]mentioning
confidence: 99%